(untitled) (International Journal on Stereo & Immersive Media, 2022)
Photography studies have not always been dedicated to the analysis of photographic studios to better understand the works of great photographers. This essay focuses on the different photographic studios of Carlos Relvas (1838-1894) in Golegã, with a particular focus on the little-studied and littleknown transformations of his splendorous Photographic Atelier of Golegã into a residential space. In the 1870s, the paradigm shift of photosensitive emulsions to faster exposure times had an impact on the way Carlos Relvas looked at his studio, forcing him to rethink the investment made in a space that no longer corresponded to the new technical reality of photography. Understood as a light production machine, Carlos Relvas’ studio is a key piece in his photographic work. In this essay, through the analysis of his photographs, we recover details and aspects of his various studios that are revealing of his inventive spirit, as well as his desire to keep up with the evolution of photographic art.